2008
DOI: 10.1017/s0001924000002554
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on spiked body in hypersonic flow

Abstract: A spike attached to a hemispherical body drastically changes its flowfield and influences aerodynamic drag in a hypersonic flow. It is, therefore, a potential candidate for drag reduction of a future high-speed vehicle. The effect of the spike length, shape, spike nose configuration and angle-of-attack on the reduction of the drag is experimentally studied with use of hypersonic wind-tunnel at Mach 6. The effects of geometrical parameters of the spike and angle-of-attack on the aerodynamic coefficient are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 14 publications
3
54
0
Order By: Relevance
“…The drag reduction experienced by spiked blunt bodies was explained by the size of the recirculation zone, which screens a considerable portion of the main body [1,3,12]. Increasing the spike length causes the reattachment point to move further downstream along the main body surface and the recirculation zone to expand, covering a larger area of the main body; consequently, a further drag drop is achieved.…”
Section: Models With Sharp Spikesmentioning
confidence: 99%
See 2 more Smart Citations
“…The drag reduction experienced by spiked blunt bodies was explained by the size of the recirculation zone, which screens a considerable portion of the main body [1,3,12]. Increasing the spike length causes the reattachment point to move further downstream along the main body surface and the recirculation zone to expand, covering a larger area of the main body; consequently, a further drag drop is achieved.…”
Section: Models With Sharp Spikesmentioning
confidence: 99%
“…1c. It has been proved that a spike with an aerodisk overperformed the plain pointed aerospike in terms of drag and aerodynamic heating reduction [1][2][3][4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Menezes et al [4] tested the e ectiveness of spikes on blunt faced cones at M = 5:75, and could achieve a drag reduction of the order 65% with a at faced aerodisc spike. Mach 6.0 experiments with variations in geometrical parameters of spike and di erent shapes were tested by Kalimuthu et al [5], who reported that the aerodisc con guration performed better than aerospikes. However, in the same line, Kalimuthu and Rathakrishnan [6] reported that with a hemispherical aerospike at L=D = 2:0, there was a drag reduction of about 78%.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Konstantin and Federico [9] conducted the numerical simulations with respect to it. Kalimuthu et al [10] conducted the experiment about drag reduction, using blunt bodies with hemispherical, flat and pointed aerodisks in hypersonic flow condition. Their results were also validated by Mehta [11].…”
Section: Introductionmentioning
confidence: 99%